Dampak Perilaku Bullying Terhadap Perkembangan Anak Ditingkat Sekolah Dasar - Septika Laily Anti; Chairul Amriyah (Mathematics Education Study Program, 2025)
The purpose of this research is to 1) identify the factors influencing the occurrence of bullying behavior on the development of children at the elementary school level 2) identify the forms of bullying behavior on the development of children at the elementary school level 3) understand the impact of bullying behavior on the development of children at the elementary school level. This research is a literature review using a comprehensive strategy method. The subject of this research is journals related to bullying behavior in elementary schools. From this research, it is concluded that bullying behavior has a significant impact on the development of children in elementary school, both psychologically, socially, and academically. Educational institutions need to enhance the prevention of bullying behavior by collaborating with parents, the community, alumni, students, educators, and teachers so that schools can have a safe environment for activities.